Karya Tari Ngarepat: Sumber ide dan konsep Rejang Kapat di Desa Timbrah, Kabupaten Karangasem. - Dipasatyadewi, Ni Luh; Sariada, I Ketut; Satyani, Ida Ayu Wayan Arya (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2024)
This Ngarepat Dance work comes from rejang kapat in Timbrah Village, Karangasem Regency. One of the aims of the Ngarepat Dance work was created to educate the wider community about the processions or ceremonial rituals carried out by prospective kelihan dahe before becoming kelihan dahe. The kelihan dahe rejang kapat is a symbol of the four dedari, Dewe Dedari Agung, Dewe Dedari Suci, Dewe Dedari Kendran, Dewe Dedari Tohok. So it gets the title Ngarepat. Taken from two words ngarep which means foremost, Utama: he is the father. And Pat which means the word number four which refers to the word kapat which means the fourth Balinese month. To produce maximum work, assistance from supervisors and partners is needed. The partner chosen is Sanggar Paripurna, Sanggar Paripurna can provide shelter and guidance in the process of creating this dance work. The method used in this creation process is Angripta Sesolahan by I Kt. Suteja, in the book there are six methods for creating a work, namely planning, nuasen, makalin, lesin, ngebah and presentation. From this process, a form and form of work is produced, Ngarepat consists of 6 (six) female dancers, the make-up used is minimalist, the dress code uses wastra or cloth with the dominant color white as a symbol of purification and MIDI (musical instrument digital interface) music. . This work also gives rise to several novelties, one of which is the novelty of the movements obtained by the creator, such as the kapat movement, agem ngarepat and ngeyeg. The creator hopes that this work can be useful for the general public.